Identity Crisis in Reza Ghasemi’s The Nocturnal Harmony of Wood Orchestra - Niloofar Mansouri; Samira Sasani (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2020)
ABSTRACTMigration, this multifaceted phenomenon, has always been a concept of importance in different domains such as art and literature. What impacts migration has on human psychology can be well elaborated on using the tool of characterization in stories. Among these impacts, the one regarding identity is probably of highest importance. Therefore, the literature of diaspora can be a field for exploring the process of identity refashioning. What the present study aims to elaborate on is Reza Ghasemi’s The Nocturnal Harmony of Wood Orchestra and the way identity crisis is manifested in and handled by the characters in this book. The analysis is grounded on Homi Bhabha’s concept of Third-Space but to specifically analyze the challenges that immigrant characters face in this liminal location, Yuri Lotman’s cultural idea of semiosphere is also incorporated. Keywords: Identity Crisis, Literature of Diaspora, Reza Ghasemi, Third-Space, Yuri Lotman